2011
DOI: 10.4161/cbt.12.3.17033
|View full text |Cite
|
Sign up to set email alerts
|

Quinacrine sensitizes hepatocellular carcinoma cells to TRAIL and chemotherapeutic agents

Abstract: Quinacrine has been widely explored in treatment of malaria, giardiasis, and rheumatic diseases. We find that quinacrine stabilizes p53 and induces p53-dependent and independent cell death. Treatment by quinacrine alone at concentrations of 10-20 mM for 1-2 d cannot kill hepatocellular carcinoma cells, such as HepG2, Hep3B, Huh7, which are also resistant to TRAIL. However, quinacrine renders these cells sensitive to treatment by TRAIL. Co-treatment of these cells with quinacrine and TRAIL induces overwhelming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 29 publications
5
43
1
Order By: Relevance
“…Moreover, quinacrine-induced NFκB inactivation promotes TRAIL, oxaliplatin and 5-fluorouracil cytotoxicity in human colon carcinoma cell lines via growth inhibition (Jani et al, 2010;Gallant et al, 2011). Consistently, quinacrine is a chemosensitizer that can enhance chemotherapeutic drug-induced apoptosis of cancer cells (Friedman et al, 2007;Wang et al, 2010Wang et al, , 2011Wu et al, 2012). Noticeably, quinacrine-induced chemosensitization is primarily attributed to altered BCL2 family protein expression (Jani et al, 2010;Wang et al, 2010Wang et al, , 2011Gallant et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…Moreover, quinacrine-induced NFκB inactivation promotes TRAIL, oxaliplatin and 5-fluorouracil cytotoxicity in human colon carcinoma cell lines via growth inhibition (Jani et al, 2010;Gallant et al, 2011). Consistently, quinacrine is a chemosensitizer that can enhance chemotherapeutic drug-induced apoptosis of cancer cells (Friedman et al, 2007;Wang et al, 2010Wang et al, , 2011Wu et al, 2012). Noticeably, quinacrine-induced chemosensitization is primarily attributed to altered BCL2 family protein expression (Jani et al, 2010;Wang et al, 2010Wang et al, , 2011Gallant et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…9 We thereafter determined that quinacrine could sensitize hepatocellular carcinoma to TRAIL through the induction of DR5. 10 We also showed that quinacrine, in combination with sorafenib, could synergize to significantly diminish levels of Mcl-1 protein, an anti-apoptotic Bcl-2 family member that is essential for tumor survival in many types of human tumors. 11 Together, these data supported further exploration of quinacrine as an anticancer agent.…”
Section: Quinacrine Synergizes With 5-fluorouracil and Other Therapiementioning
confidence: 95%
“…We have shown that quinacrine can overcome the resistance of hepatocellular carcinoma cells to TRAIL and a wide array of chemotherapies. 10 It has also been shown that quinacrine can synergize with chemotherapy in a variety of other systems. 26,27 Given its broad spectrum of activity, we thus hypothesized that quinacrine could enhance, if not synergize, with both conventional chemotherapeutic agents and targeted therapies in colorectal cancer.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…It should be noted that sensitivity of cancer cells to TRAIL-mediated apoptosis is determined by multiple factors and that resistance mechanisms often involve intracellular regulators of apoptosis such as Mcl-1 or cFLIP. Our lab and others have reported on synergistic combinations of TRAIL and chemotherapy or targeted agents to overcome such resistance mechanisms (21)(22)(23). Such combinations should be explored with DR4 Atrimer complexes to overcome potential resistance mechanisms and expand their activity profile.…”
Section: Discussionmentioning
confidence: 99%